2020
DOI: 10.1002/jtr.2429
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modelling of inter‐relationship between tourism, energy consumption, CO2 emissions and economic growth in South Asia

Abstract: Tourism is an important economic driver and plays a critical role in the economic development of South Asian countries. However, tourism also brings about some inevitable consequences on the environmental quality of these countries. Using the Autoregressive Distributed Lags, Vector Error-Correction Model and Panel frameworks, we investigate the inter-relationships between tourism, energy consumption, CO 2 emissions and gross domestic product (GDP) in South Asia, using data for the period 1990-2014. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 42 publications
4
27
3
Order By: Relevance
“…The existing literature on energy economics generally focuses on the link between economic growth, energy, tourism, and carbon emissions [36][37][38][39][40][41][42][43][44][45][46]. The nexus between tourism and energy has been a neglected topic, with a relatively smaller strand of literature studying the relationship between energy consumption and the tourism sector ignoring CO 2 [47][48][49].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on energy economics generally focuses on the link between economic growth, energy, tourism, and carbon emissions [36][37][38][39][40][41][42][43][44][45][46]. The nexus between tourism and energy has been a neglected topic, with a relatively smaller strand of literature studying the relationship between energy consumption and the tourism sector ignoring CO 2 [47][48][49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated unidirectional causality running from tourist arrivals to energy consumption in the long run. Selvanathan et al [44] too investigated the inter-relationships between tourism, energy consumption, carbon emissions and GDP for South Asian countries. The research applied panel ARDL and VECM frameworks with data from 1990 to 2014 and concluded that tourism positively affected energy consumption in Bangladesh, India, Nepal and Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, this study contributes to the limited literature that has assessed the validity of the EKC hypothesis using the per capita ecological footprint (EF) figures to proxy for environmental quality in the South Asian context. The preceding EKC studies on South Asia have conventionally quantified environmental quality in terms of the carbon dioxide (CO 2 ) emission levels [17][18][19]. However, using CO 2 emissions does not cover the multidimensional aspects of environmental adversities experienced across South Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tourist arrivals and departures increase energy-related CO2 emissions (Amin et al, 2020;Dogan and Aslan, 2017;Liu et al, 2019). International tourism revenues positively affect economic growth by increasing net exports (Aratuo et al, 2019;Brida et al, 2020;Eyuboglu and Uzar, 2020;Leitão and Lorente, 2020;Selvanathan et al, 2020). As economic growth stimulates consumption and investment expenditures, energy demand expands.…”
Section: Introductionmentioning
confidence: 99%